Design and Research of Intelligent Safety Monitoring Robot for Coal Mine Shaft Construction. (23rd June 2021) - Fu, Wenjun; Xu, Ying; Liu, Liangping; Zhang, Liang
Abstract : This study analyzes the main causes of accidents in the period of coal mine shaft construction and the shortage of the existing safety monitoring technology, puts forward the intelligent safety monitoring robot technology based on shaft construction, and deeply investigates the functions that the safety monitoring robot should have. Besides, the research objective of intelligent safety monitoring robot for shaft construction is pointed out, and the research is carried out from such aspects as the robot body structure, walking mechanism, adsorption mechanism, control, communication, intelligent sensing, hazard source recognition, recognition of explosive detonators, and software platform development. As well, this study designs the technical device of intelligent safety monitoring robot for shaft construction, defines the characteristics of this technology, expounds the important significance of studying this technology, and indicates the development trend of this technology.